Shine your light: The life and lessons of Madeline Woleg - Naomi Sunderland; Phil Graham; Joel Spence; Rae Cooper; Kayla Harris (2021)
This output is part of a suite of self-published, peer reviewed community and creative resources from the Australian Research Council funded Remedy Project: First Nations music as a determinant of health